The Effectiveness of Kepok Banana Peel (Musa paradisiaca var. bluggoe L) As Liquid Organic Fertilizer Against Pakcoy Plants (Brassica rapa L) - Devi Anugrah; Pulia Tiaresa Prastamay (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Kepok banana peel (Musa paradisiaca var. bluggoe L) which is wasted will result in environmental pollution, but now the kepok banana peel can be used as liquid organic fertilizer in the growth of Pak Choy (Brassica rapa L) plants. This study aims to determine the effectiveness of the kepok banana peel (Musa paradisiaca var. bluggoe L) as a liquid organic fertilizer on the growth of Pak Choy (Brassica rapa L). This research was conducted at the Green House PT. Floraterusbersemi, in East Jakarta from March–July 2022. The research method used is an experimental method with the research design using a Completely Randomized Design (CRD). This research was conducted by giving 6 treatments and 5 repetitions, where there were three parameters used, namely plant height, number of leaves, and plant wet weight. The treatment in question was P0 as (control) without giving kepok banana peel liquid organic fertilizer P1 = 10 ml, P2 = 25 ml, P3 = 50 ml, P4 = 75 ml, P5 = 100 ml kepok banana peel liquid organic fertilizer. Treatments are given once a week. The results of this study showed that the growth of Pak Choy plants in the P2 treatment had the most effect on plant height of 21.7 cm, the number of leaves 12.6 leaves, and wet weight of 17.62 g. So it can be concluded that the use of kepok banana peels as a liquid organic fertilizer affects the growth of Pak Choy (Brassica rapa L)